The Digital Fortress: Navigating Cybersecurity Challenges in Connected Medical Devices - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The rapid integration of Artificial Intelligence AI and the Internet of Medical Things IoMT has revolutionized healthcare, promising unprecedented efficiency...
Keywords: Digital Health; Patient Care; Artificial Intelligence; Healthcare Innovation